Comparative Law in the Jurisprudence of the Supreme Court of Canada - Rason, Nino Olivetti; Pennicino, Sara (Judicial Cosmopolitanism, 2019)
"Comparative Law in the Jurisprudence of the Supreme Court of Canada" published on 09 Sep 2019 by Brill | Nijhoff.